2016
DOI: 10.1111/jir.12296
|View full text |Cite
|
Sign up to set email alerts
|

Physical health issues in adults with severe or profound intellectual and motor disabilities: a systematic review of cross‐sectional studies

Abstract: This review provides an overview of the current state of the art research on the prevalence of health problems in adults with SPIMD. There is a substantial need for comprehensive epidemiological data in order to find clusters of health problems specific for people with SPIMD. This would provide insight into the excess morbidity associated with SPIMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 46 publications
(130 reference statements)
1
59
3
1
Order By: Relevance
“…). In a recent systematic review, meta‐analysis indicated a prevalence of 16%, which is lower compared with the current study (Van Timmeren et al ., in press). Gastro‐oesophageal reflux is known to have non‐specific symptoms and is frequently overlooked (Bohmer et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). In a recent systematic review, meta‐analysis indicated a prevalence of 16%, which is lower compared with the current study (Van Timmeren et al ., in press). Gastro‐oesophageal reflux is known to have non‐specific symptoms and is frequently overlooked (Bohmer et al .…”
Section: Discussionmentioning
confidence: 99%
“…). In addition, the prevalence of dysphagia (47%) was in accordance with previous studies (Van Timmeren et al ., in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In persons with CP, evaluation of sensory function is also difficult compared to motor function due to an inability to communicate. However, previous studies have revealed that sensory dysfunctions such as visual, hearing and olfactory impairments frequently exist in persons with CP . Sensory cells, synapses, afferent nerves and the central nervous system must be evaluated to determine the presence of a sensory dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…). They frequently suffer from general health problems and sensory impairments (van Timmeren, van der Schans, van der Putten, Krijnen, Steenbergen, van Schrojenstein Lantman‐de Valk & Waninge, under review). Persons with PIMD do therefore fully depend on their environment (Nakken & Vlaskamp ).…”
Section: Introductionmentioning
confidence: 99%